Copyright Governance for Online Short Videos: Perspective of Transaction Cost Economics - Long, Mingxia (Frontiers in Psychology, 2022)
In recent years, the copyright governance of short videos has become a hot issue of common concern in the academic community and the industry. Therefore, this study intends to explore the economic aspect of copyright governance for the proliferation of infringing short videos. The short video industry of China has been taken as a case to show the copyright governance issue. Transaction cost theory has been applied to analyze the economic aspect of copyright governance in terms of four dimensions: bounded rationality, opportunism, environmental uncertainty, and asset specificity. From the perspective of transaction cost economics, it is observed that the problem of short video infringement is essentially a market failure due to high transaction costs. In the short video market, the legal transaction of the copyright requires substantial transaction costs. Transaction costs are too high, especially when transaction costs exceed the net proceeds that short video users initially expected from the authorization, making the transaction impossible to occur and lead to infringement. To effectively control the infringement of short videos, it is necessary to build a cross-platform information-sharing mechanism to reduce search costs, establish a unified copyright management platform to reduce coordination costs, and give full attention to the role of technical support to reduce regulatory costs.